Causes of death and heart pathology in pacemaker or implantable cardioverter-def ibrillator patients who died in hospital - Dvořák, Petr; Novák, Miroslav; Kamarýt, Pavel; Slaná, Bronislava; Lipoldová, Jolana; Dvořák, Pavel; Veselý, Karel (Soudni lekarstvi, 2014)
UNLABELLED: 83 pacemaker (PM)/14 implantable cardioverter-defibrillator (ICD) autopsied patients, predominantly males, deceased 4.0±3.0/2.8±2.5 years after implantation in hospital. Coronary artery disease was most frequent. Its consequences were more severe in ICD patients. Sclerotic and rheumatic heart changes were present in older PM patients group only. The immediate cause of death was mostly of cardiac etiology. Relatively short implant-death interval should be explained by rather great part of non-cardiac causes of death in hospitalised patients. KEYWORDS: pacemakers - implantable cardioverter - defibrillators-causes of death - heart pathology - autopsy.